La Temmassonge: Tokoh Kunci Pengembangan Islam di Kerajaan Bone Abad ke-18 - Amal, Arsy; M. Dahlan (Rihlah : Jurnal Sejarah dan Kebudayaan, 2024)
During the reign of La Temmasonge Sultan Abdul Razak Jalaluddin, the 22nd King ofBone, he was known as a leader with a strong social conscience and a deep concern for thedevelopment of Islam in the Bone Kingdom. This study aims to analyze the role of LaTemmasonge in the development of Islam in the Bone Kingdom in the 18th century. Theresearch methods used include heuristics, source criticism, interpretation, and historiography.The findings indicate that, as a socially-minded leader, La Temmasonge actively strengthenedIslamic values through the development of markets, rice fields, fish ponds, and mosques. Thedevelopment of markets, rice fields, and fish ponds advanced the local economy, createdbusiness opportunities, and strengthened social interactions. Meanwhile, the construction ofmosques supported access to religious education and reinforced Islamic identity in thecommunity. La Temmasonge’s strategies had impacts not only on religious aspects but alsobrought significant changes to the social, economic, and political order in the SulawesiPeninsula.